The Effect of Group Guidance Using Modeling Techniques to Reduce Online Game Addiction in SMK Negeri 1 Sukamara - Prasetio, Lukman; Handayani, Arri; Widiharto, Chr. Argo (CV. Rayyan Dwi Bharata, 2023)
The background of this research is that students are often sleepy during class hours, students often fall asleep during distance learning so they don't participate, students' school grades decrease, parents or guardians of students say that while at home their children play online games more often, students spend time playing games. from after the evening prayer until just before dawn, students forget to eat and worship because they are preoccupied with playing online games, students also experience imsonia (sleep disturbance), the purpose of this study is to determine the effect of group guidance with modeling techniques to reduce online game addiction for students of SMK Negeri 1 Sukamara . The research method used is true experimental with pretest-posttest control group design. The population in this study were all students of class XI ATPH SMK Negeri 1 Sukamara, totaling 65 students consisting of two classes, namely class XI ATPH 1 and XI ATPH 2. The try out will be held in class XI ATPH 1 with a total of 32 students. The sampling technique used is simple random sampling technique. The analysis used to test the validity is the product moment and reliability using the alpha formula. The final conclusion is based on the results of data analysis that the pretest results in the experimental group with an average of 45.8 and the control group with an average of 50.1, while the posttest results in the experimental group with an average of 63.3 and the control group with an average average 59.8. In addition, from the results of the t-test analysis, the difference between the posttest between the experimental group and the control group for online game addiction using the t-test formula was obtained at 10.3 ttable at 2.021 at a significant level of 5%, so tcount is greater than the mean ttable, meaning Ho is rejected and Ha is accepted, so that it can be concluded by going through the hypothesis that says